2022
DOI: 10.1177/01455613221124773
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Platelet Rich Plasma in the Olfactory Cleft for COVID-19 Patients With Persistent Olfactory Dysfunction: Description of the Technique

Abstract: In this paper, we described technique of platelet rich plasma injection into the olfactory cleft in a 22-year-old female with 24-month post–COVID-19 anosmia. The technique starts with the blood extraction and the isolation of PRP through a 10-min centrifugation. The supernatant was injected in nasal regions after a local anesthesia through a 0° rigid optic. Several points of .2–.5 mL were performed in the nasal septum in regard of the head of the middle turbine and in the head of the middle turbine in both sid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…TGF-β oversees the remodeling phase, where collagen synthesis by fibroblasts fortifies tissue strength and integrity. These growth factors also serve as chemotactic signals, recruiting macrophages and stem cells to the injury site and emphasizing PRP's role in tissue repair and regeneration [53][54][55]. The fibrin matrix's scaffolding effect and the modulation of inflammation by PRP contribute to reduced healing time and improved recovery outcomes [56].…”
Section: Definition Composition Of Prp and Molecular Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β oversees the remodeling phase, where collagen synthesis by fibroblasts fortifies tissue strength and integrity. These growth factors also serve as chemotactic signals, recruiting macrophages and stem cells to the injury site and emphasizing PRP's role in tissue repair and regeneration [53][54][55]. The fibrin matrix's scaffolding effect and the modulation of inflammation by PRP contribute to reduced healing time and improved recovery outcomes [56].…”
Section: Definition Composition Of Prp and Molecular Mechanismsmentioning
confidence: 99%
“…Different PRP injection techniques are described in the research; some use a single injection, while others use repeated injections spaced out over a shorter period of time [54][55][56][57][58][59]. Most injections were administered at outpatient facilities or hospital based setting, and the frequency of treatment sessions ranged from a single application to multiple injections over a period of up to six weeks.…”
Section: Prp Protocol Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory and regenerative potential of PVRP offered an option of treat persistent viral inflammation of neuroepithelium. Injections of PVRP into the olfactory area for COVID-19 patients with persistent olfactory dysfunction were administered by Lechien et al and Steffens et al [ 246 , 247 ]. Both studies showed encouraging results, with most patients reacquiring the sensation of smell.…”
Section: Use Of Plasma Rich With Platelets and Extracellular Vesicles...mentioning
confidence: 99%
“…There was only 1 practitioner that carried out the injection for European patients. The procedure was described in 2 recent papers, 13,20 and is reported in Supplemental Appendix 3, available online. In sum, the blood extraction was performed into a 20 mL tube with sodium citrate anticoagulant.…”
Section: Injection Procedures and Outcomesmentioning
confidence: 99%